Marimba instrument construction from Kayu malam wood (Diospyros maingayi) - Sinin, Hamdan; Hasnizam, Abdul Wahid; Iran Amri, Musoddiq; Nyawai, Yohanes (North Carolina State University, 2018)
This work investigated the possibility of using a local wood Kayu malam (Diospyros maingayi) to construct a marimba, a musical instrument. The marimba was constructed as similar as possible to the commercial rosewood marimba. The sound and established frequencies were compared with a commercial rosewood marimba. The findings showed that although the peak value of the spectrum from the prototype marimba differs from pitch to pitch, it is useful to note that the prototype marimba was tuned according to piano standard. The commercial marimba only has peaks at the lower end of the spectrum whereas the prototype marimba contained peaks up until the higher end of its spectrum. The marimba made of Kayu malam (D. maingayi) produced the same pitch as the marimba made of rosewood.